THE ROLE OF FAMILY AND COMMUNITY IN THE LIFESTYLE OF THE NEW GENERATION - M. Mirsaidova (International Engineering Journal For Research & Development, 2020)
In this newspaper article loving for the motherland honesty, bringing up the young generatio with rich outlook and knowlandge and such kind of ideas are wnit ten.